Implementasi Metode Hybrid Case-Based Reasoning Untuk Mendiagnosa Pengidap Penyakit Post-Traumatic Stress Disorder(PTSD) - Erdina Daniati Simanjuntak; Hery Sunandar; Rivalri Kristianto Hondro (JURIKOM (Jurnal Riset Komputer), 2020)
Post Traumatic Stress Disorder is a mental condition where a person experiences panic attacks that are triggered by past experience trauma. Having a traumatic event is a hard thing for anyone. Health services to the community are needed to support a healthy lifestyle. Limitations of health services in the community that are inadequate have a lot of negative impacts on some people who suffer from an illness, especially mental disorders caused by several events. This limitation will become an obstacle due to lack of health infrastructure in terms of consultation of the disease so that sufferers do not know the symptoms such as what they have experienced and how far the disease has been identified, so it is very much needed a solution and alternative in handling the problem of limited health services. By building a system that can help people with the disease, is expected to provide solutions for people with disease to take an action or consultation with an expert based on the system.